2005
DOI: 10.1111/j.1440-1584.2005.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Do health and medical workforce shortages explain the lower rate of rural consumers' complaints to Victoria's Health Services Commissioner?

Abstract: Reduced opportunity to use health services due to rural health and medical workforce shortages was the best-supported explanation for the lower rural complaint rate. Workforce shortages impact on the quality of rural health services and on residents' opportunities to improve their health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…It might also be questioned how accurately women recalled their experiences during a vulnerable time or whether people in rural areas do not report negative views of health professionals or services in their community. Yet, Jones found that there was no evidence to support the view that rural consumers are reluctant to report complaints or accept lesser quality services 23 …”
Section: Discussionsupporting
confidence: 88%
“…It might also be questioned how accurately women recalled their experiences during a vulnerable time or whether people in rural areas do not report negative views of health professionals or services in their community. Yet, Jones found that there was no evidence to support the view that rural consumers are reluctant to report complaints or accept lesser quality services 23 …”
Section: Discussionsupporting
confidence: 88%
“…An analysis of 23 000 records of enquiries made by people throughout Victoria to the Health Services Commissioner (HSC) between 1988-2001 revealed a 25% under-representation of rural complaints, [14][15] suggesting that rural residents may be less dissatisfied or less willing to express dissatisfaction with their health care services than metropolitan residents. The analysis also revealed differences in the issues of complaints by location, with rural residents making relatively more complaints about communication, rights and access issues, and fewer about treatment than metropolitan residents.…”
Section: What Are the Implications For Practitioners?mentioning
confidence: 99%
“…The results provide several significant insights into previously published research based on the secondary analysis of complaint data. 10,11 The study did, however, have some limitations. While falling within expectations for the method used, the survey response rate was relatively low.…”
Section: Discussionmentioning
confidence: 96%
“…Lack of access to health services and the consequent reduced opportunities to utilise health care have been identified as a probable partial explanation of this difference, along with a lack of consumer knowledge about the complaints process. 11,12 The survey also sought to validate the findings from a series of focus groups conducted in the Loddon-Mallee region of Victoria in which participants identified lack of access to health services as the area most likely to generate complaints from rural consumers. In addition, lack of awareness of available complaint mechanisms, along with scepticism about the role of complaints in bringing about change, were the reasons consumers would not make complaints in unsatisfactory situations.…”
Section: Quality Improvementmentioning
confidence: 99%